IN SILICO STUDY OF BIOACTIVE COMPOUNDS FROM SUNGKAI (PERONEMA CANESCENS) AS IMMUNOMODULATOR - RAHARDHIAN, MUHAMMAD RYAN RADIX; SUSILAWATI, YASMIWAR; MUSFIROH, IDA; FEBRIYANTI, RADEN MAYA; MUCHTARIDI; SUMIWI, SRI ADI (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to predict a bioactive compound from Peronema canescens (PC) with mechanisms inhibitor interleukin 6 (IL-6) and tumor necrosis factor-alpha (TNF-α) potential as an immunomodulatory using in silico approach. Methods: Autodock 4 was used to accomplish computer-assisted drug design with molecular docking simulation to discover binding energy, inhibition constant, and interactions with an amino acid in bioactive compounds from PC against IL-6 and TNF-α receptors. Lipinski predicts the drug-likeness of a bioactive compound for the oral route of administration. ADMET profiling of bioactive compounds to predict pharmacokinetic properties with pkCSM ADMET. Results: The results showed that the best binding energy, inhibition constant, and interactions with an amino acid of peronemin C1 against IL-6 and TNF-α receptors were (-7.19 kcal/mol; 5.39 nM; Arg 179, Arg 182, Gln 175), and (-8.86 kcal/mol; 320.42 nM; Tyr 119, Tyr 59, and Gly 121), respectively. All bioactive compounds from PC met Lipinski's rule of five requirements for oral administration. ADMET prediction results all bioactive compounds from PC are non-mutagenic, except peronemin D1 is mutagenic. Conclusion: The peronemin C1 bioactive compounds from PC have good immunomodulatory potential, effectively inhibiting human IL-6 and TNF-α receptors using in silico approach.